Determinants of Ownership and Utilization of Insecticide-Treated Bed Nets for Malaria Control in Eastern Ethiopia. (7th November 2012) - Biadgilign, Sibhatu; Reda, Ayalu; Kedir, Haji
Abstract : Background . Malaria remains a major cause of mortality and morbidity in the world, and particularly in sub-Saharan Africa. Objectives . The aim of this study was to determine ownership and utilization of ITNs among households with children under five in the previous night. Methods . A community based cross-sectional study was conducted in Gursum district in Eastern Ethiopia. A total of 335 households were surveyed using a pretested structured questionnaire administered though house-to-house interviews. Results . Household ownership for at least one mosquito net and use of nets were 62.4% (95% CI 57.2–67.6%) and 21.5% (95% CI 17.1–25.9%), respectively. Households who received or were told about ITN in the last 6 months were three times more likely to have used it than those who were not (OR 3.25; 95% CI 1.5–7.10). Households whose heads were engaged as a farmer (adjusted OR 0.137; 95% CI: 0.04–0.50) and housewife (OR 0.26; 95% CI: 0.08–0.82) were less likely to use ITN than those of other occupations. Conclusion . The findings indicate low ITN ownership and utilization among the households. Intensive health education and community mobilization effort should be employed to increase the possession and proper utilization of insecticide treated bed nets.